Находки половецких каменных изваяний в северной части Ергеней - Панасюк, Н.В.; Усачук, А.Н. (Степи Европы в эпоху средневековья, 2012)
Летом 2005 г отдельным отрядом (начальник Н.В.Панасюк) Степной археологической экспедиции ГИМ (начальник Н.И.Шишлина) проводились разведки на территории Ремонтненского р-на Ростовской обл. (Россия). В ходе разведок были осмотрены курганные группы и отдельные насыпи в районе балки Темрта, а также берега р.Джурак-Сал в месте впадения в нее вышеуказанной балки . В ходе проведения работ от местных жителей была получена информация о наличии в балке Рассыпной “каменных баб”. In summer 2005 during prospecting along the Juraq-Sal river bank the workers of the Steppe archaeological expedition of the State Historical Museum found the fragments of 3 statues near Rassypnaia gully. It is notable that the fragments of two statues were found at the bottom of a pond. All the statues are made of different kinds of local sandstone. Statue 1 belongs to type V (by Pletniova S.A., 1974). The sex and type (sitting or semi-sitting) of the statue cannot be indicated definitely since it is fragmented. Statue 2, by S.A.Pletniova, belongs to type IV. Statue 3, despite a small size of the fragment preserved, can be obviously recognized as a male image.